Genome of a stage-dependent cave-dwelling frog reveals the genetic mechanism of an extremely divergent biphasic life cycle - Ningning Lu; Wei Zhu; Chen-Yang Tang; Chaochao Yan; Qiheng Chen; Wei Wu; Liming Chang; Jianping Jiang; Jia-Tang Li; Bin Wang (Cell Reports)
Summary: Cave-dwelling species offer unique insights into adaptive evolution. The stage-dependent cave frog, Oreolalax rhodostigmatus (Orho), exhibits troglomorphic traits as a tadpole in Karst caves, transitioning to a troglophilic/trogloxenic lifestyle after metamorphosis, characterized by developed pigment and eyes. We present the Orho genome (3.16 Gb, 26,192 protein-coding genes), revealing extensive expansion and positive selection in gene families associated with olfactory, taste, visual, and pain perceptions. Orho tadpoles exhibit suppressed visual function while retaining crystalline lens development. Adult eyes demonstrate high light-induced plasticity in the visual cycle. Orho tadpoles display both developmental and light-induced melanogenesis, which is associated with distinctive tyrosinases. A stage-dependent amphibian-specific tyrosinase subfamily, reported here, underpins their ontogenetic pigmentation. Additionally, prominent hepatic fat storage and genetic/transcriptional variations in lipid metabolism genes characterize tadpole development. These findings unveil the molecular mechanisms behind Orho’s stage-dependent cave adaptation, which differs mechanistically from cavefishes, offering valuable insights into the highly divergent biphasic life cycle.